THE INFLUENCE OF BODY TYPE, STRENGTH, AND FLEXIBILITY ON INJURY OCCURRENCE AMONG STOK BINA GUNA STUDENTS IN ARTISTIC GYMNASTICS SUBJECT - Lubis, Hafiz Yazid; Isnandar, Muhammad; Waruwu, Rahmad Sentosa; Sillaban, Putra Anugrah (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2024)
Objectives—This pilot project, aimed at investigating body type, strength, and flexibility as risk factors for injury amongst Bina Guna College of Sports and Health Students, has yielded significant findings. Methods—Fifteen subjects volunteered to participate in the present study. An ex-post facto study design using independent samples was employed. Injury history was established through the use of a questionnaire. From this information, each individual's injury status was categorized as